Bibliometric Mapping of Constitutional Law Research: Global Trends and Indonesian Context (2000–2024) - Judijanto, Loso (Westscience Press, 2025)
This study performs a bibliometric analysis of international constitutional law research from 2000 to 2024 utilizing data from the Scopus database. The study utilizes VOSviewer and Bibliometrix to delineate author collaboration networks, institutional connections, and theme progression. Results demonstrate that constitutional law, human rights, jurisprudence, and constitutional courts represent the field's most significant themes, indicating a transition from conventional doctrinal discussions to multidisciplinary and global viewpoints. The United States, United Kingdom, Germany, Italy, and Spain lead in publishing production and international collaboration. The results underscore the globalization of constitutional study and its alignment with governance, rights, and transnational legality challenges. This research enhances comprehension of the intellectual framework, collaboration dynamics, and developing trends in constitutional law, providing valuable insights for scholars, institutions, and governments aiming to bolster academic connectedness and comparative discourse.